Multi‐institutional review of non‐hypospadiac penile urethral stricture management and outcomes. (3rd February 2022) - Abramowitz, David; Sam, Andre‐Philippe; Pachorek, Mark; Ruel, Nora; Martins, Francisco; Angulo, Javier; Simhan, Jay; Li, Eric; Nikolavsky, Dmitriy; Policastro, Connor; Ramirez‐Perez, Erick; Burks, Frank; et al.
Abstract : Objectives: Penile urethral stricture disease not associated with hypospadias is rare, and there is a wide range of commonly used surgical repair techniques for this disease. We sought to compile a multi‐institutional database of patients who had surgical correction of strictures in the penile urethra not limited to the meatus, and who had no history of hypospadias, for analysis using the Trauma and Urologic Reconstructive Network of Surgeons length, urethral segment and etiology classification system. Methods: A retrospective database from 13 institutions was compiled of patients who had undergone surgical correction of Trauma and Urologic Reconstructive Network of Surgeons length, urethral segment and etiology urethral stricture segments S2b/S2c and excluding E5, with a minimum follow‐up time of 4 months. Failure was defined as cystoscopically confirmed recurrence of a stricture measuring less than 16‐Fr. Results: We analyzed 222 patients with a median age of 57 years and a follow‐up of 49 months. The overall surgical success rate was 80.2%. On multivariate analysis, the two variables identified that were predictive of surgical success were stricture length ≤2 cm as well as use of a buccal mucosa graft as compared to use of a fasciocutaneous flap, which had success rates of 83% and 52%, respectively ( P = 0.0004). No statistically significant differences were found based on incisional approach or surgical technique, nor were outcomes different based on etiology or preoperative patient demographics. Conclusions: Surgical repair of penile urethral strictures of non‐hypospadiac origin have a favorable overall success rate, at 80.2%. Regardless of incisional approach or surgical technique, all operations appear to have similar outcomes other than repairs using fasciocutaneous flap, which were statistically less successful than those using buccal mucosa graft.